Inhibition of ERK1/2 downregulates triglyceride and palmitic acid accumulation in cashmere goat foetal fibroblasts. Issue 1 (1st January 2018) - Feng, Xue; Bao, Lili; Wu, Manlin; Zhang, Di; Yao, Le; Guo, Zhixin; Yan, Dandan; Zhao, Pingping; Hao, Huifang; Wang, Zhigang
ABSTRACT: An extracellular signal-regulated kinase (ERK) is a mitogen-activated protein kinase (MAPK) in mammalian cells that interact with the mechanistic target of rapamycin (mTOR) signalling pathway. ERK signalling integrates signals from growth factors, nutrients, and mitogens to regulate cell proliferation, differentiation, and the cell cycle. The purpose of this study was to examine the inhibitory effects of U0126, a specific MEK/ERK inhibitor, on ERK and mTOR signalling, Lipin 1 protein level, PPARγ activation, and triglyceride (TAG) and palmitic acid (PA) accumulation in Cashmere goat foetal fibroblasts (GFbs). The proliferation of GFbs was significantly impeded by U0126, the IC50 of which was 1.54 µM. U0126 prevented the phosphorylation of ERK1/2 (Thr202/Tyr204), S6 (Ser240/244), and 4EBP1 (Thr37/46), the latter 2 of which are mTOR downstream effectors. Moreover, the cytoplasmic level of Lipin 1 and the nuclear PPARγ protein abundance were attenuated by U0126 while the concentration of TAG and PA was significantly decreased ( p < .05) in GFbs. These data indicate that ERK1/2 have important functions in GFb proliferation, governing the activation of PPARγ and Lipin 1 level and the accumulation of TAG and PA.